A Coupled Biomorpho‐Geomechanical Model of Tidal Marsh Evolution. Issue 11 (1st November 2019) - Zoccarato, C.; Da Lio, C.; Tosi, L.; Teatini, Pietro
Abstract: Ecogeomorphic characteristics of tidal marshes are strongly related to their elevation with respect to the mean sea level. Predicting the long‐term evolution and resilience of such ecosystems in times of rapid natural and anthropogenic climate changes is of critical importance. The notion that the tidal marsh elevation is the result of feedbacks between vegetation dynamics, sediment fluxes, natural consolidation, and sea‐level changes is widely recognized. However, the interaction of these processes has been poorly investigated until now. This contribution aims at presenting a novel numerical model to simulate the above‐surface and subsurface coupled dynamics of a tidal landscape in a 2‐D‐framework, with the relative sea‐level rise (RSLR) acting as an external stressor. A biomorphological model is used to compute deposition fluxes, which depends on topography and availability of organic/inorganic sediments. The outcome is used as forcing term in a physically based geomechanical model to simulate the consolidation of the marsh body that, in turn, influences sediment fluxes by acting on the platform elevation. The results demonstrate how compaction of the marsh body can crucially affect the resilience of tidal landforms to RSLR accelerations. With normal sediment concentration in coastal waters (10< C 0 <100 mg/l), if minerogenic (stiff) deposits prevail, a tidal marsh is capable of maintaining its elevation relative to mean sea level independently of RSLR (at least up to 10 mm/yr). When the marsh is composed of a large percentage of more compressible organic matter, the landform resilience is much more dependent on RSLR, implying higher vulnerability with respect to future climate changes. Key Points: A novel numerical model is proposed to simulate accretion and natural consolidation of tidal marshes The feedbacks between surface and subsurface processes are investigated through a coupling approach Compaction of the marsh body crucially affects the landform elevation and, in turn, its resilience to relative sea level rise